2002
DOI: 10.1124/mol.62.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Human β-Globin Gene Expression in Murine and Human IVS2–654 Thalassemic Erythroid Cells by Free Uptake of Antisense Oligonucleotides

Abstract: Correct human ␤-globin mRNA has been restored in erythroid cells from transgenic mice carrying the human gene with ␤-globin IVS2-654 splice mutation and from thalassemia patients with the IVS2-654/␤ E genotype. This was accomplished in a dose-and time-dependent manner by free uptake of morpholino oligonucleotide antisense to the aberrant splice site at position 652 of intron 2 in ␤-globin pre-mRNA. Under optimal conditions of oligonucleotide uptake, the maximal levels of correct human ␤-globin mRNA and hemoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 26 publications
1
44
0
1
Order By: Relevance
“…We have found that repair of splicing-defective thalassemic pre-mRNA and concomitant production of adult hemoglobin (HbA) can be accomplished ex vivo in erythroid progenitor cells from thalassemic patients treated with SSOs with modified backbones (10,11), including peptide-conjugate morpholino, SSO 654-P005 (data not shown). Thus, this treatment is compatible with and effective in the human cells that will constitute its target in the clinic.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have found that repair of splicing-defective thalassemic pre-mRNA and concomitant production of adult hemoglobin (HbA) can be accomplished ex vivo in erythroid progenitor cells from thalassemic patients treated with SSOs with modified backbones (10,11), including peptide-conjugate morpholino, SSO 654-P005 (data not shown). Thus, this treatment is compatible with and effective in the human cells that will constitute its target in the clinic.…”
Section: Resultsmentioning
confidence: 99%
“…The profiles of morpholino and PNA-4K oligonucleotides, including their sequences, were reported elsewhere (11,14,15). The 18-mer morpholino (5Ј-GCTATTACCTTAACCCAG-3Ј)-peptide-[(D)R(D)RRQRRKKRFFC] conjugate (P005) antisense to the aberrant 5Ј splice site in the IVS2-654 ␤-globin pre-mRNA was synthesized at AVI BioPharma.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Les auteurs avaient obtenu la restauration d'un épissage correct en ciblant en système acellulaire, soit le site 5' nouvellement créé, soit le site 3' cryptique activé. Dans les années suivantes, le bien-fondé de cette approche a été vérifié expérimentalement dans des systèmes cellulaires : cellules HeLa, puis précurseurs érythroïdes de sujets thalassémiques [16][17][18][19]. Le passage à l'expérimentation animale in vivo a été franchi grâce à des souris transgéniques dont un des deux locus bêta globine avait été remplacé par le locus bêta humain portant la mutation IVS2-654 [20] [20] ont reçu pendant 3 semaines (4 jours consécutifs, 3 jours d'arrêt) par injection intraveineuse (25 mg/kg) un oligonucléotide antisens long de 18 nt dirigé contre la mutation IVS2-654 (Figure 1).…”
unclassified